FARS1‐related disorders caused by bi‐allelic mutations in cytosolic phenylalanyl‐tRNA synthetase genes: Look beyond the lungs!. Issue 6 (28th February 2021) - Schuch, Luise A.; Forstner, Maria; Rapp, Christina K.; Li, Yang; Smith, Desiree E. C.; Mendes, Marisa I.; Delhommel, Florent; Sattler, Michael; Emiralioğlu, Nagehan; Taskiran, Ekim Z.; Orhan, Diclehan; Kiper, Nural; et al.
Abstract: Aminoacyl‐tRNA synthetases (ARSs) catalyze the first step of protein biosynthesis (canonical function) and have additional (non‐canonical) functions outside of translation. Bi‐allelic pathogenic variants in genes encoding ARSs are associated with various recessive mitochondrial and multisystem disorders. We describe here a multisystem clinical phenotype based on bi‐allelic mutations in the two genes ( FARSA, FARSB ) encoding distinct subunits for tetrameric cytosolic phenylalanyl‐tRNA synthetase (FARS1). Interstitial lung disease with cholesterol pneumonitis on histology emerged as an early characteristic feature and significantly determined disease burden. Additional clinical characteristics of the patients included neurological findings, liver dysfunction, and connective tissue, muscular and vascular abnormalities. Structural modeling of newly identified missense mutations in the alpha subunit of FARS1, FARSA, showed exclusive mapping to the enzyme's conserved catalytic domain. Patient‐derived mutant cells displayed compromised aminoacylation activity in two cases, while remaining unaffected in another. Collectively, these findings expand current knowledge about the human ARS disease spectrum and support a loss of canonical and non‐canonical function in FARS1‐associated recessive disease. Abstract : Bi‐allelic variants in the two genes ( FARSA, FARSB ) encoding distinct subunits of tetrameric cytosolic phenylalanyl‐tRNA synthetase (FARS1) cause a similar clinical phenotype that affects multiple organ systems.